Investigating extreme marine summers in the Mediterranean Sea - Dimitra Denaxa; Gerasimos Korres; Emmanouil Flaounas; Maria Hatzaki (Ocean Science, 2024)
The Mediterranean Sea (MS) has undergone significant surface warming, particularly pronounced during summers and associated with devastating impacts on marine life. Alongside the ongoing research on warming trends and marine heatwaves (MHWs), here we address the importance of understanding anomalously warm conditions also on the seasonal timescale. We propose the concept of extreme marine summers (EMSs) and investigate their characteristics in the MS, using sea surface temperature (SST) reanalysis data spanning 1950–2020. We define EMSs at a particular location, as the summers with a mean summer SST exceeding the 95th percentile. A marine summer may become extreme, under various SST substructures. Results show that, in most of the basin, EMSs are formed primarily due to the warmer summer days being warmer than normal. Areas where the warmest (coldest) part of the SST distribution is more variable experience EMSs primarily due to the warmest (coldest) part of the distribution being anomalously warm. MHWs occurring within EMSs are more intense, longer lasting, and more frequent than usual mainly in the northern MS regions. These enhanced MHW conditions occur mainly within the warmest part of the SST distribution. By means of temporal coverage of MHW conditions, a more pronounced occurrence of MHWs in EMSs is found for the central and eastern basin where up to 55 % of MHW days over 1950–2020 fall within EMSs. The role of air–sea heat fluxes in driving EMSs is quantified through a newly proposed metric. Results suggest that surface fluxes primarily drive EMSs in the northern half of the MS, while oceanic processes play a major role in southern regions. Upper-ocean preconditioning also contributes to the formation of EMSs. Finally, a detrended dataset was produced to examine how the SST multi-decadal variability affects the studied EMS features. Despite leading to warmer EMSs basin-wide, the multi-decadal signal does not significantly affect the dominant SST substructures during EMSs. Results also highlight the fundamental role of latent heat flux in modulating the surface heat budget during EMSs, regardless of the long-term trends.

The Mediterranean Forecasting System – Part 1: Evolution and performance - Giovanni Coppini; Emanuela Clementi; Gianpiero Cossarini; Stefano Salon; Gerasimos Korres; Michalis Ravdas; Rita Lecci; Jenny Pistoia; Anna Chiara Goglio; Massimiliano Drudi; Alessandro Grandi; Ali Aydogdu; et al. (Ocean Science, 2023)
The Mediterranean Forecasting System produces operational analyses and reanalyses and 10 d forecasts for many essential ocean variables (EOVs), from currents, temperature, salinity, and sea level to wind waves and pelagic biogeochemistry. The products are available at a horizontal resolution of 1/24∘ (approximately 4 km) and with 141 unevenly spaced vertical levels. The core of the Mediterranean Forecasting System is constituted by the physical (PHY), the biogeochemical (BIO), and the wave (WAV) components, consisting of both numerical models and data assimilation modules. The three components together constitute the so-called Mediterranean Monitoring and Forecasting Center (Med-MFC) of the Copernicus Marine Service. Daily 10 d forecasts and analyses are produced by the PHY, BIO, and WAV operational systems, while reanalyses are produced every ∼ 3 years for the past 30 years and are extended (yearly). The modelling systems, their coupling strategy, and their evolutions are illustrated in detail. For the first time, the quality of the products is documented in terms of skill metrics evaluated over a common 3-year period (2018–2020), giving the first complete assessment of uncertainties for all the Mediterranean environmental variable analyses.

The POSEIDON Ocean Observing System: Technological Development and Challenges - Manolis Ntoumas; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Paris Pagonis; Maria Sotiropoulou; Manolis Pettas; Evi Bourma; Sylvia Christodoulaki; Dimitris Kassis; et al. (Journal of Marine Science and Engineering, 2022)
Advanced marine observation infrastructures are the most significant scientific tool for the study of marine ecosystem trends and shifts. Ocean monitoring technologies, though highly demanding and expensive, are essential for the monitoring and long-term study of oceanic systems. The POSEIDON system for monitoring and forecasting the marine environment is an augmented research infrastructure, unique in the Eastern Mediterranean basin, contributing to the European Ocean Observing System implementation, focusing—among others—on biogeochemical observations and deep-sea ecosystem and geological processes. The technological evolution of the POSEIDON system through a science-coupled strategy supported by engineers and scientists, resulted in a state-of-the-art ocean observing system. There has been a continuous expansion of the infrastructure with new scientific platforms and supporting facilities. Innovative sensing technologies were introduced in the operational data acquisition and new methodologies and tools were developed to improve the system operations and efficiency. As a part of the scientific community of ocean observatories, POSEIDON contributes actively to the improving of the ocean observing. International access to engineering and field demonstrating services, data products and technology testing facilities has been offered to scientists and industry partners. POSEIDON is a widely recognizable international technology testing/demonstrating node specializing in marine technology providing high-level services.

The Hellenic Marine Observing, Forecasting and Technology System—An Integrated Infrastructure for Marine Research - Evi Bourma; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Vassilis Zervakis; Elina Tragou; Petros Katsafados; Christos Spyrou; Manos Dassenakis; Serafim Poulos; et al. (Journal of Marine Science and Engineering, 2022)
Research infrastructures have been established throughout Europe in order to create robust organizations that will facilitate and enhance research and innovation processes and will advance society with innovative products and services. The Hellenic Integrated Marine Observing, Forecasting and Technology System (component of HIMIOFoTS RI) has been implemented in the framework of the National Roadmap for Research Infrastructures to form a large-scale infrastructure for the marine environment in Greece. It links together ocean observing and forecasting systems, coastal zone monitoring and management practices, as well as ocean engineering testing facilities. The overarching framework of the system supports the coordination of five organizations with expertise in the field of marine science and technology, the central management of research activities, and the common development of services and products. It comprises facilities and resources while it provides open access to research communities (academia, industry) to support the scientific advancements and innovation in their fields. The Hellenic Marine Observing, Forecasting and Technology System was further enhanced during its implementation through significant upgrades and developments in order to extend its observing capacity and the forecasting and technological abilities, while advancing the provided services and products.

Recent hydrological status of the Aegean Sea derived from free drifting profilers - DIMITRIS KASSIS; GERASIMOS KORRES (Mediterranean Marine Science, 2021)
Being a semi-enclosed basin of the Mediterranean Sea, the Aegean Sea comprises a complex hydrology that plays a significant role in the hydrology of the Eastern Mediterranean Sea. Its interaction with many sub-basins, along with its contribution towards the formation of deep and intermediate water, makes it an ideal case for the study of hydrological changes in transitional areas. Since 2010, the operational monitoring of the basin has been significantly enriched due to the deployment of autonomous free-drifting profilers (Argo floats) under the framework of the newly formed Greek Argo Research Infrastructure activities. In this study the hydrological status of the area is examined for the period 2010 - 2017 using the temperature and salinity profiles acquired from Argo floats that operated in the basin. The profiles are analyzed together with complementary remote sensing and model outputs datasets in order to present the spatio-temporal distribution of the co-existent water masses and shed light on hydrological features and changes that took place throughout the basin in an attempt to reassess its hydrological status during the last decade. The distribution of the physical properties in different sub-regions and their interaction is examined reconstructing a general picture of strong latitudinal gradients in the T-S and σθ fields from the upper layers towards the deeper zones. Interannually, findings indicate changes of the Aegean water masses structure within the water-column. Deep homogenization in the upper layers is recorded mainly during the winter periods of 2011-2012, 2014-2015 and 2016-2017 in the southern, central, and northern parts of the area accordingly. The observed dense water formation events, along with mixing and advection appear to alterate the water column physical properties structure and affect the dynamics of the surface and sub-surface dominant water masses in the Aegean. The results further highlight the valuable information that can be extracted from the operation of free-drifting profilers in enclosed marginal seas similar to the Aegean case.

One-year assessment of the two-way coupled atmosphere-ocean wave modeling system CHAOS over the Mediterranean and Black Seas - GEORGE VARLAS; CHRISTOS SPYROU; ANASTASIOS PAPADOPOULOS; GERASIMOS KORRES; PETROS KATSAFADOS (Mediterranean Marine Science, 2020)
Nowadays, it has become clear that atmosphere and ocean should be simulated by integrated modeling systems resolving interconnected physical factors which determine Earth’s energy balance. Waves play a key role on the interfacial interaction between atmosphere and ocean regulating momentum, heat and moisture exchange. This study aims to evaluate the two-way coupled atmosphere-ocean wave system CHAOS (Chemical Hydrological Atmosphere Ocean wave System) over the Mediterranean and Black Seas. The evaluation is performed against in-situ and remote sensing data for the period from 1 December 2013 to 1 December 2014. CHAOS includes the Weather Research Forecasting (WRF) model version 3.8 as atmospheric component and the Wave model (WAM) cycle 4.5.4 as ocean wave component, coupled through the OASIS3-MCT coupler version 3.0. In order to assess the impact of the atmosphere-ocean waves coupling, two approaches of continuous model simulations are followed. In the first approach (1-way coupling mode) the ocean wave component uses the winds produced by the atmospheric component while in the second approach (2-way coupling mode) the atmospheric component additionally uses the sea state information estimated by the ocean wave component through wave-dependent Charnock parameter computations. In the 2-way coupling mode, the attenuation of the atmospheric flow has a damping effect on wind-generated waves. The simulations in 2-way coupling mode produce more realistic results yielding statistical improvements. Against buoys observations, 2-way reduces root mean square error (RMSE) per 1.2% and 6.3% for wind speed and significant wave height, respectively, while against Jason-2 satellite retrievals per 0.5% and 2.4%, respectively. Additionally, the 2-way outperforms the 1-way coupling mode under intense wind and wave conditions during this one-year period.

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Using canonical correlation analysis to produce dynamically based and highly efficient statistical observation operators - Eric Jansen; Sam Pimentel; Wang-Hung Tse; Dimitra Denaxa; Gerasimos Korres; Isabelle Mirouze; Andrea Storto (Ocean Science, 2019)
Observation operators (OOs) are a central component of any data assimilation system. As they project the state variables of a numerical model into the space of the observations, they also provide an ideal opportunity to correct for effects that are not described or are insufficiently described by the model. In such cases a dynamical OO, an OO that interfaces to a secondary and more specialised model, often provides the best results. However, given the large number of observations to be assimilated in a typical atmospheric or oceanographic model, the computational resources needed for using a fully dynamical OO mean that this option is usually not feasible. This paper presents a method, based on canonical correlation analysis (CCA), that can be used to generate highly efficient statistical OOs that are based on a dynamical model. These OOs can provide an approximation to the dynamical model at a fraction of the computational cost. One possible application of such an OO is the modelling of the diurnal cycle of sea surface temperature (SST) in ocean general circulation models (OGCMs). Satellites that measure SST measure the temperature of the thin uppermost layer of the ocean. This layer is strongly affected by atmospheric conditions, and its temperature can differ significantly from the water below. This causes a discrepancy between the SST measurements and the upper layer of the OGCM, which typically has a thickness of around 1 m. The CCA OO method is used to parameterise the diurnal cycle of SST. The CCA OO is based on an input dataset from the General Ocean Turbulence Model (GOTM), a high-resolution water column model that has been specifically tuned for this purpose. The parameterisations of the CCA OO are found to be in good agreement with the results from the GOTM and improve upon existing parameterisations, showing the potential of this method for use in data assimilation systems.

Assessing the impact of Argo floats temperature measurements on the numerical weather prediction forecast skill - GEORGE VARLAS; PETROS KATSAFADOS; GERASIMOS KORRES; ANASTASIOS PAPADOPOULOS (Mediterranean Marine Science, 2019)
The forecast skill of numerical weather prediction (NWP) models relies, among other factors such as the prediction itself and the assimilation scheme, on the accuracy of the observations utilized in the assimilation systems for the production of initial and boundary conditions. One of the most crucial parameters in weather forecasting is the sea surface temperature (SST). In the majority of NWP models, the initial and lower boundary conditions involve gridded (SST) analyses which consist of data obtained by buoys, ships and satellites. The main aim of this study is to integrate Argo temperature measurements in gridded SST analyses and to assess their impact on the forecast skill of a limited area atmospheric model. Argo floats are “state-of-the-art” oceanographic instruments producing high-quality temperature profiles for the ice-free ocean. In this study, Argo temperatures are incorporated into gridded SST fields without applying any smoothing method in order to directly assess the impact of Argo temperatures on numerical weather prediction. Their impact is assessed under intense weather cyclonic conditions at the Mediterranean Sea by performing two sensitivity simulations either incorporating or not Argo temperatures into gridded SST fields used in the generation of the initial and lower boundary conditions. The results indicate that the inclusion of Argo-measured near-surface temperatures in the lower boundary condition modifies the surface heat fluxes, thus affecting mean sea level pressure and precipitation. In particular, an overall improvement of the precipitation forecast skill up to 3% has been demonstrated. Moreover, the incorporation of Argo temperatures affects the simulated track and intensity of the cyclone over the Balkan Peninsula.

An integrated open-coastal biogeochemistry, ecosystem and biodiversity observatory of the eastern Mediterranean – the Cretan Sea component of the POSEIDON system - George Petihakis; Leonidas Perivoliotis; Gerasimos Korres; Dionysios Ballas; Constantin Frangoulis; Paris Pagonis; Manolis Ntoumas; Manos Pettas; Antonis Chalkiopoulos; Maria Sotiropoulou; Margarita Bekiari; Alkiviadis Kalampokis; et al. (Ocean Science, 2018)
There is a general scarcity of oceanic observations that concurrently examine air–sea interactions, coastal–open-ocean processes and physical–biogeochemical processes, in appropriate spatiotemporal scales and under continuous, long-term data acquisition schemes. In the Mediterranean Sea, the resulting knowledge gaps and observing challenges increase due to its oligotrophic character, especially in the eastern part of the basin. The oligotrophic open Cretan Sea's biogeochemistry is considered to be representative of a greater Mediterranean area up to 106 km2, and understanding its features may be useful on even larger oceanic scales, since the Mediterranean Sea has been considered a miniature model of the global ocean. The spatiotemporal coverage of biogeochemical (BGC) observations in the Cretan Sea has progressively increased over the last decades, especially since the creation of the POSEIDON observing system, which has adopted a multiplatform, multivariable approach, supporting BGC data acquisition. The current POSEIDON system's status includes open and coastal sea fixed platforms, a Ferrybox (FB) system and Bio-Argo autonomous floats that remotely deliver fluorescence as a proxy of chlorophyll-a (Chl-a), O2, pH and pCO2 data, as well as BGC-related physical variables. Since 2010, the list has been further expanded to other BGC (nutrients, vertical particulate matter fluxes), ecosystem and biodiversity (from viruses up to zooplankton) variables, thanks to the addition of sediment traps, frequent research vessel (R/V) visits for seawater–plankton sampling and an acoustic Doppler current profiler (ADCP) delivering information on macrozooplankton–micronekton vertical migration (in the epipelagic to mesopelagic layer). Gliders and drifters are the new (currently under integration to the existing system) platforms, supporting BGC monitoring. Land-based facilities, such as data centres, technical support infrastructure, calibration laboratory and mesocosms, support and give added value to the observatory. The data gathered from these platforms are used to improve the quality of the BGC-ecosystem model predictions, which have recently incorporated atmospheric nutrient deposition processes and assimilation of satellite Chl-a data. Besides addressing open scientific questions at regional and international levels, examples of which are presented, the observatory provides user-oriented services to marine policy makers and the society, and is a technological test bed for new and/or cost-efficient BGC sensor technology and marine equipment. It is part of European and international observing programs, playing a key role in regional data handling and participating in harmonization and best practices procedures. Future expansion plans consider the evolving scientific and society priorities, balanced with sustainable management.

Coupling hydrodynamic and wave models: first step and sensitivity experiments in the Mediterranean Sea - Emanuela Clementi; Paolo Oddo; Massimiliano Drudi; Nadia Pinardi; Gerasimos Korres; Alessandro Grandi (Ocean Dynamics, 2017)

Hydrodynamic features of the South Aegean Sea as derived from Argo T/S and dissolved oxygen profiles in the area - Dimitris Kassis; Evangelia Krasakopoulou; Gerasimos Korres; George Petihakis; George S. Triantafyllou (Ocean Dynamics, 2016)

Hydrodynamic variability of the Cretan Sea derived from Argo float profiles and multi-parametric buoy measurements during 2010–2012 - Dimitris Kassis; Gerasimos Korres; George Petihakis; Leonidas Perivoliotis (Ocean Dynamics, 2015)

Wave climate of the Hellenic Seas obtained from a wave hindcast for the period 1960–2001 - Anna Zacharioudaki; Gerasimos Korres; Leonidas Perivoliotis (Ocean Dynamics, 2015)